Used part dealers' acceptance of remanufactured ELV components in Malaysia's national car industry - Wan Mahmood, Wan Hasrulnizzam; Mansor, Muhd Ridzuan; Suhaimin, Mohd Khairul Nizam; Azmi, Mohd Azham; Abdul Salaam, Hadi; Mohd Shapri, Ahmad Husni (Human Resource Management Academic Research Society, 2025)
An End-of-Life Vehicle (ELV) is defined as the vehicle that is not operational anymore, is too old or too damaged beyond economical repair, and repairs are not worth the costs anymore. In Malaysia, the high volume of vehicles in use has increased the number of ELVs. Used Part Dealers (UPDs) help manage the components of ELVs in the country. The expectations and acceptance of remanufactured ELV products by UPDs was the focus of this research, specifically on Malaysia’s national cars, the Proton Wira. Qualitative data was collected through field observations and semi-structured interviews while structured surveys involving 33 UPDs provided quantitative data. The acceptance of remanufactured products was highly positive. More than 90% of respondents agreed on the following claims: part prices should be based on the condition of the part (EX5: 93.9%)), proper dismantling documentation is needed (EX12: 100%), and ELV environmentally unsound practices should be avoided (EX7: 91%). In addition, over 87% of UPDs expressed preference for remanufactured parts from Proton Wira, specifically for high-value remanufactured components which included the gearbox (93.9%), alternator (93.9%), and distributor (93.9%). The factor analysis further substantiated these findings (KMO = 0.512; Bartlett’s Test, p < 0.001), confirming that acceptance in the market is widespread, thus statistically significant. These findings highlight the value of UPDs in the promotion of sustainable automotive practices in terms of offering inexpensive substitutes to new components. This study highlights the increasing industrial significance of ELV remanufacturing and serves as a resource for policymakers, industry players, and advocates of sustainability on the need to reinforce the ELV management in Malaysia.